Why Do We Need Writers’ Stories About History to Do Research Into the Past? - Švedas , Aurimas (Colloquia, 2018)
Basing himself on samples from Lithuanian and world literature the author of the article discusses seven aspects by which literary texts are important for historians in the twenty-first century.Aspect I. Society can create an emotional relationship with the past with the help of a writer’s text. The past becomes history when we experience it as reality that is dramatically different from the known and understandable present.Aspect II. A writer’s text can quite often becomes a historical source for representatives of various historiographical schools who study man’s activities, thinking, behaviour and everyday life in very different ways.Aspect III. Thanks to the writers in the totalitarian, authoritarian and democratic societies subjects and issues, which historians themselves cannot discuss for some reason or other, are introduced into the public space.Aspect IV. Writers’ contribution can be significant for appeasing traumatised individual memory and reconciling conflicting memories of different communities depicting conflicts through the prism of individual lives.Aspect V. In the twenty-first century, writers and historians become equal partners discussing the ways of history making, workings of individual and collective memory as well as the principles of creating narratives about the past.Aspect VI. Some texts of fiction that are concerned with the issues of historical knowledge, historical identity and the workings of memory, in the opinion of part of history theoreticians can be considered a specific postmodern or post postmodern way of writing history, which in certain cases may be equated with historiography.Aspect VII. Writers with lively historical imagination can be particularly important discourse partners when the historians’ community sets out on discussing the “What would happen if …” issue and on alternative history research.
Keywords: history; literature; historical novel; unconventional historiography; historical imagination